2020
DOI: 10.1002/dneu.22786
|View full text |Cite
|
Sign up to set email alerts
|

Migration and fate of vestibular melanocytes during the development of the human inner ear

Abstract: Melanocytes are present in various parts of the inner ear, including the stria vascularis in the cochlea and the dark cell areas in the vestibular organs, where they contribute to endolymph homeostasis. Developmental studies describing the distribution of vestibular melanocytes are scarce, especially in humans. In this study, we investigated the distribution and maturation of the vestibular melanocytes in relation to the developing dark cell epithelium in inner ear specimens from week 5 to week 14 of developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Tissue was obtained at the developmental stages W13 ( n = 1) and W17 ( n = 1). Inner ears were fixed in 4% paraformaldehyde, decalcified and embedded in paraffin as previously described (van Beelen et al, 2020 ). Sections (5 μm) were cut using a HM 355S rotary microtome (Thermo Fisher Diagnostics).…”
Section: Methods and Results Of Clinical Genetic Testing And Immunohi...mentioning
confidence: 99%
“…Tissue was obtained at the developmental stages W13 ( n = 1) and W17 ( n = 1). Inner ears were fixed in 4% paraformaldehyde, decalcified and embedded in paraffin as previously described (van Beelen et al, 2020 ). Sections (5 μm) were cut using a HM 355S rotary microtome (Thermo Fisher Diagnostics).…”
Section: Methods and Results Of Clinical Genetic Testing And Immunohi...mentioning
confidence: 99%
“…Studies made by van Beelen et al showed that before 7 week of embriogenesis vestibular melanocytes are localised around the utricle and the ampullae in the inner ear. Melanocytes in the saccule were not observed in any of the developmental stages of the inner ear during embryogenesis [5,6].…”
Section: Introductionmentioning
confidence: 85%
“…Melanocytes of the vestibular system can mainly be found in the dark cell area of the utricle and the ampulla of the semicircular canals [ 22 ], closely aligned with the dark cells. In fact, it is uncommon to find them in the saccule and the other semicircular canals, because of the absence of dark cell epithelium in these locations.…”
Section: Discussionmentioning
confidence: 99%